Defining an action-research's content to improve a policy supporting indigents' health in Mali: a concept mapping - Mathieu Seppey; Laurence Touré; Valéry Ridde (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Concept mapping (CM) is a method used to create consensus around a concept within a group of actors, which enables an empowering process for the participants through dialogues and shared information. We performed a CM, aiming to improve the operationalisation of a health policy, the RAMED, to promote healthcare access to the indigent population in Mali. # Methods The CM followed five steps leading to the conceptual map development: 1) brainstorming, 2) statements' scoring, 3) clustering, 4) statistical (hierarchical clustering and multi-dimensional scaling) and qualitative analysis, and 5) validating the map. Twenty-seven participants took place in the CM, representing eighteen organisations linked to the implementation of the policy. # Results We identified seven clusters of activities towards finding the concrete and collective solutions to improve healthcare access: "funding strengthening," "integral management and care of indigents," "expertise creation," "promotion and communication," "indigents' identification processes," "monitoring and evaluation," and "integration and coordination of actors." According to scalability and priority scores, "identification processes" was the most scalable and important cluster (3.03 \[±0.51\] and 3.26 \[±0.47\]/4 respectively), while "funding strengthening" was the least scalable and important (2.59 \[±0.47\] and 2.76 \[±0.42\]/4 respectively). # Conclusions Although this method is primarily exploratory and a great starting point for further collaborative research, it managed to highlight the two fundamental issues in action-research: the difficulty related to the knowledge transfer to vulnerable populations and their lack of participation in the research process. It is particularly an issue in West Africa, due to lack of empirical studies and high poverty levels. Results of this study demonstrate that CM offers an important starting point for improvements, which should focus on knowledge transfer and inclusion of vulnerable populations' points of view.